Pension funds, capital markets, and the power of diversification - Stewart, Fiona; Despalins, Romain; Remizova, Inna (Washington, DC, 2017)
"The potential for pension funds to contribute to capital markets and thereby economic growth has been argued on a theoretical basis and demonstrated empirically. However, reforms fostering the development of funded pension systems have not had the economic impact hoped for in some countries. Pension fund portfolios in some cases have remained highly exposed to shorter-term assets, such as bank deposits and shorter-term government bonds. This, in turn, has led to relatively low investment returns, thereby potentially affecting income adequacy in retirement. This paper looks at the potential regulatory hurdles to long-term investment by pension funds, while also proposing international diversification and the creation of domestic investment opportunities to help portfolio diversification and ultimately improve the delivery of secure, adequate pensions."